Pulmonary Function Tests and Their Reversibility in Smokers - Ghanshyam B Borisagar; Jayant B Chauhan (Medsci Publications, 2014)
Background: Smoking is known as the major cause of chronic obstructive pulmonary disease (COPD) where most of pulmonary function tests (PFTs) especially those indicating the diameter of airways are reduced. In this study, PFTs of smokers were compared with those of nonsmokers, and the effect of bronchodilator inhaler (salbutamol) on PFTs of smokers was also examined. Methods: Pulmonary function tests were measured in 97 male smokers and compared with 95 male nonsmokers. Forced vital capacity (FVC), forced expiratory volume in one second (FEV1), maximal mid-expiratory flow (MMEF), peak expiratory flow (PEF), maximal expiratory flow at 75%, 50%, and 25% of the FVC (MEF75, MEF50, and MEF25 respectively) were measured. In addition, pulmonary function tests of 33 male smokers before and 10 minutes after administration of 200 μg salbutamol inhaler were measured. Results: Most values of PFTs in smokers were significantly lower than those of non-smokers (p<0.001 for FVC, FEV1, PEF, MEF75, p<0.01 for MMEF, and p<0.02 for MEF50). Significant correlations between the smoking duration and FEV1, PEF, MEF75, and MEF50 (p<0.05 to p<0.01) was found, but correlations between smoking quantity and values of PFTs were not significant. All values of PFTs were significantly increased after salbutamol administration (p<0.05 to p<0.01). Conclusion: The profound effect of smoking on PFT showed that smoking leads to constriction of large and medium sized airways which is mostly due to duration not to quantity of smoking. The airway constriction in smokers was reversible which, was mostly seen for medium sized airways.